A novel online prognostic tool to predict long‐term survival after liver resection for intrahepatic cholangiocarcinoma: The "metro‐ticket" paradigm. Issue 2 (19th April 2019) - Sahara, Kota; Tsilimigras, Diamantis I.; Mehta, Rittal; Bagante, Fabio; Guglielmi, Alfredo; Aldrighetti, Luca; Alexandrescu, Sorin; Marques, Hugo P.; Shen, Feng; Koerkamp, Bas G.; Endo, Itaru; Pawlik, Timothy M.
Abstract: Background: The aim of the current study was to develop an online calculator to predict survival after liver resection for intrahepatic cholangiocarcinoma (ICC) based on the "metro‐ticket" paradigm. Methods: Between 1990 and 2016, patients who underwent liver resection for ICC were identified in an international multi‐institutional database. The final multivariable model of survival was used to develop an online prognostic calculator of survival. Results: Among 643 patients, actual 5‐year overall survival (OS) after resection for ICC was 42.7%. On multivariable analysis, CA19‐9 > 200 (hazard ratio (HR), 2.62; 95% CI, 2.01‐3.42), sum of the number and largest tumor size >7 (HR, 1.88; 95% CI, 1.46‐2.42), N1 disease (HR, 2.87; 95% CI, 1.98‐4.16), R1 resection (HR, 1.72; 95% CI, 1.21‐2.46), poor/undifferentiated tumor grade (HR, 1.74; 95% CI, 1.25‐2.44), major vascular invasion (HR, 1.47; 95% CI, 1.03‐2.10), and adjuvant chemotherapy (HR, 0.64; 95% CI, 0.45‐0.89) were significantly associated with survival and were included in the online calculator. The predictive accuracy of the model was good to very good as the C‐statistics to predict 5‐year OS was 0.696 in the training dataset and 0.672 with bootstrapping resamples (n = 5000) in the test dataset. Conclusion: A novel, online calculator was developed to estimate the 5‐year survival probability for patients undergoing resection for ICC. This tool could help provide useful information to guide treatment decision‐making and inform conversations about prognosis.